POTENSI PROFIT INVESTASI PADA SAHAM SYARIAH LQ45 PADA TAHUN 2018-2023 DI BURSA EFEK INDONESIA - Totok Adhi Prasetyo (At-Tawazun, Jurnal Ekonomi Syariah, 2023)
The main purpose of investing is to generate and increase profits in the form of a certain amount of money. Profit considerations for investors will influence the outcome of investment planning decisions. A new challenge for Muslim investors is whether investing in Islamic stocks can generate better returns and minimize risk. Or the risk is greater than the return achieved. Problems that often occur in the field experienced by investors are misjudging and analyzing the shares purchased, weak knowledge about shares, failing to make profits (Capital Loss), not getting capital again, not getting dividends, the company is not liquid. Seeing this phenomenon, it is necessary to analyze the profit level of investing in LQ45 sharia shares in the Indonesian Capital Market. This type of research is descriptive quantitative and correlative with a literature study approach with secondary data as a source of data. Based on the results of descriptive analysis within a period of 5 years, it shows that the average return of Islamic stocks is - 0.010424062 or -1%. There are 17 sharia stock companies, there are 10 companies that get negative returns so that it has an impact on the overall average return of sharia shares.